The Role of The Store Atmosphere To Impulsive Purchasing (Study in Matahari Cilandak Town Square) - Mamlu Atul Hasanah; Prasetyo Hadi; Hariyanto Ridwan (AFEBI Management and Business Review, 2017)
Impulsive purchases is one factor, which are considered by retailers and manufacturers. The purpose of this study was to determine the role of positive emotions in mediating the store atmosphere on impulsive purchases. The population in this study is the community in Cilandak West district which often make impulsive purchases in Matahari Cilandak Town Square. The size of the samples which are taken by as many as 50 people, with a non-probability sampling method particularly purposive sampling. Data is collected through questionnaires. The data analysis technique used is the PLS (Partial Least Square) method of analysis. These results indicate that the store atmosphere has a positive and significant impact on impulsive purchases at 0.387. Indirect effect store atmosphere of impulsive purchases through positive emotion at 0.431. Hence the indirect effect has more impact on the direct effect.Keywords: Impulsive Purchases, Positive Emotion, Store Atmosphere